Production Decline Analysis and Forecasting in Tight-Gas Reservoirs - Mahadik, M.; Bahrami, Hassan; Hossain, Mofazzal; Tsar Mitchel, P. (Australian Petroleum Production and Exploration Association, 2012)
Exponential decline curve analysis is widely used to estimate recoverable reserves due to its simplicity. In most cases, however, an exponential model cannot provide a satisfactory match of overall production history. The generalised form of a hyperbolic decline model is more powerful in matching production history than the other decline models, but it is difficult to apply in practical production data analysis since it requires predicting two unknowns as decline constants.Although a hyperbolic model may provide a good fit to early-time production decline data; it may overestimate the late-time production, especially for hydraulic fractured wells in a tight-gas reservoir. In fact, the exponential decline model might be more reliable for forecasting the late-time production. This paper presents a practical approach to production decline analysis for non-fractured and fractured wells in a tight-gas reservoir using numerical simulation. Some production rate functions and type curves are introduced to obtain the best matching values of hyperbolic, exponential and harmonic production decline constants. The simulated production rate decline data for various well and reservoir parameters are used to indicate the optimum time duration of use of each decline model and to show the time when the production decline starts following the exponential model. The proposed approach is applied in production data analysis and forecasting for a tight-gas field in WA. The results showed good agreement with the production forecast obtained from a reservoir simulation.